'I am everything but myself': exploring visual voice accounts of single mothers caring for a daughter with Rett syndrome. Issue 4 (2nd October 2019) - Williamson, Iain
ABSTRACT: Caring for a disabled child as a lone parent is complex and dynamic and can affect well-being significantly. Five single mothers caring for a daughter with Rett syndrome took photographs to document their experiences prior to taking part in extended interviews lasting one to two hours. Verbal and visual data were analysed together using interpretative phenomenological analysis. Two inter-connected themes are presented. Committing to "Total Caregiving" captures the ways in which the mothers aspired to excel at caregiving, anticipating and meeting their daughter's needs, projecting them from stigma but at considerable cost to themselves, Self-Abnegation and Existential Crisis outlines the associated psychological challenges experienced by the women—especially how they felt "fused" in a negative triad with their daughters and a personified "Retts"; a malign all-encompassing force in their lives. Applications of the findings to interventions and an evaluation of the methodologies in the context of qualitative research are offered.